Colour sorting of translucent samples - Pavlidis, George (Journal of Advanced Computer Science & Technology, 2015)
Automated quality control and sorting based on computer vision techniques has been a long celebrated practice in industrial processes and production. Among the surface characteristics that guide the decision making in such systems, the colour holds a prominent position. This gets somehow complicated in cases dealing with translucent samples or samples with a significant amount of transparency and yet distinctive colour hues. The scope of this paper is to provide a method to tackle with such cases and presents a successful application to the world-renowned mastiha of Chios, a natural aromatic translucent resin extracted from the mastic tree that grows on the island of Chios, Greece.